Electrolyte and pH-sensitive amphiphilic alginate: synthesis, self-assembly and controlled release of acetamiprid. Issue 56 (18th September 2018) - Tang, Yiyuan; Chen, Kai; Li, Jiacheng; Feng, Yuhong; Yu, Gaobo; Wang, Longzheng; Zhao, Xinyu; Peng, Yang; Zhang, Quan
Abstract : Schematic of Ugi-Alg aggregation in aqueous solution of different NaCl concentrations and pH values. Abstract : In this study, a pH-responsive amphiphilic alginate (Ugi-Alg) was synthesized via Ugi reaction without using a catalyst. The structure of Ugi-Alg was confirmed by FT-IR and 1 H NMR spectroscopy. Amphiphilic alginate can form micelles in an aqueous medium due to it's amphiphilic nature.. The impacts of Na + concentration and pH on the micelle size were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The dynamic light scattering observations showed that micelle size increases with the decrease in Na + concentration in aqueous solution. However, the micelle size decreases first and then increases as the pH value decreases from 5.3 to 2.0. Transmission electron microscopy confirmed that the mean size of micelles is 30–200 nm. In addition, a model hydrophobic pesticide (acetamiprid) was loaded in the micelles. The encapsulation efficiency and release behavior of micelles were studied, which could be controlled by Na + concentration and pH. The results indicated that encapsulation efficiency of acetamiprid increases from 55% to 96% due to the increase in Na + concentration from 0.01 M to 0.3 M. Moreover, with the decrease in pH from 5.3 to 2.0, encapsulation efficiency increases from 55% to 80%. Furthermore, the data of acetamiprid release kinetics could be well-fitted by the Weibull model.